2017
DOI: 10.1186/s13287-016-0455-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing mesoderm progenitor selection and three-dimensional microniche culture allows highly efficient endothelial differentiation and ischemic tissue repair from human pluripotent stem cells

Abstract: BackgroundGeneration of large quantities of endothelial cells is highly desirable for vascular research, for the treatment of ischemia diseases, and for tissue regeneration. To achieve this goal, we developed a simple, chemically defined culture system to efficiently and rapidly differentiate endothelial cells from human pluripotent stem cells by going through an MESP1 mesoderm progenitor stage.MethodsMesp1 is a key transcription factor that regulates the development of early cardiovascular tissue. Using an ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…H1, H9 hESCs (WiCell Institute), HUES8 hESCs (Harvard Stem Cell Institute), and human induced pluripotent stem cells (CD34-iPSCs Zhang et al 2017 ; Duan et al 2018 ), provided by Dr. J. Na, Tsinghua University) were routinely maintained on Matrigel (BD Biosciences)—coated plates (Corning) in TeSR-E8 medium (STEMCELL Technologies). hPSCs were passaged every 4 days using Accutase (Merck) and 10 μM ROCK inhibitor Y27632 (Selleck) was added for the first 24 h after passaging.…”
Section: Methodsmentioning
confidence: 99%
“…H1, H9 hESCs (WiCell Institute), HUES8 hESCs (Harvard Stem Cell Institute), and human induced pluripotent stem cells (CD34-iPSCs Zhang et al 2017 ; Duan et al 2018 ), provided by Dr. J. Na, Tsinghua University) were routinely maintained on Matrigel (BD Biosciences)—coated plates (Corning) in TeSR-E8 medium (STEMCELL Technologies). hPSCs were passaged every 4 days using Accutase (Merck) and 10 μM ROCK inhibitor Y27632 (Selleck) was added for the first 24 h after passaging.…”
Section: Methodsmentioning
confidence: 99%
“…S1C). Nfatc1 was specifically expressed in the endocardium of early developing heart at E9.5, and its expression level decreases at later embryonic and neonatal stages (Zhang et al, 2017 ). We found that Nfatc1 is expressed in the inner layer of E9.5 cKO embryonic hearts, and Pecam1 could also be obviously detected in the E9.5 cKO heart, which means both endocardium and ECs were also exist in the cKO heart (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of miRNAs on mouse or human EC function were tested by vascular tube formation and scratch-wound healing assays as described in published studies (He et al, 2008 ; Zhang et al, 2017 ). In brief, for vascular tube formation assay of mouse SVEC4–10 cells (ATCC CRL-2181 TM ), 24-well plate were pre-coated with 150 μL/well Matrigel (1:1, BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…DNA methylation and gene expression profiles of the TCGA-COAD dataset which contained 407 CRC and 46 adjacent samples were downloaded from TCGA and used as a training set. The testing set consisted of two independent DNA methylation datasets, including GSE79740 [ 12 ] which contained 44 CRC samples and 10 normal samples, and GSE42752 [ 13 ] which contained 22 CRC and 41 normal samples from GEO.…”
Section: Methodsmentioning
confidence: 99%